Expand the expressions and simplify.

5(x + 4) + 3(x + 2) =

4(x + 3) + 2(x − 4) =

4(x + 2) + 2(x + 5) =

Respones

8x+4

8x+ 26

6x+4

7x - 18

1 answer

5x + 20 + 3x + 6 = 8x + 26

4x + 12 + 2x - 8 = 6x + 4

4x + 8 + 2x + 10 = 6x + 18
Similar Questions
    1. answers icon 1 answer
  1. expand the expressions and simplify.5(x+4)+3(x+2) = 4(x+3)+2(x-4) = 4(x+2)+2(x+5)= answer choices: 6x+18 8x+4 8x+26 6x+4 7x-18
    1. answers icon 7 answers
  2. Are the expressions 3+(4x+1) and 4−4x equivalent?(1 point)Responses Yes, they are because both expressions simplify to 4−4x.
    1. answers icon 1 answer
  3. Are the expressions 3+(4x+1) and 4−4x equivalent?(1 point)Responses Yes, they are because both expressions simplify to 4−4x.
    1. answers icon 1 answer
more similar questions